PENGARUH METODE PENGAJARAN BAHASA ARAB TERHADAP MINAT BELAJAR BAHASA ARAB SISWA SMP UNISMUH MAKASSAR - Ratu Firniatul; A. Fajriwati Tajuddin (Al-Maraji' : Jurnal Pendidikan Bahasa Arab, 2018)
This study aims to determine the effect of learning methods on student learning interests, the constraints faced by students on the methods used by teachers in the teaching and learning process as well as the efforts made by students to overcome motivation on the influence of interest in learning Arabic at Junior High school Muhammadiyah of Makassar. The research method used is descriptive qualitative. Data analysis techniques use a simple percentage formula. Data collected through observation, interviews, documentation, and questionnaires. A sample of 40 students from 206 existing population. The results showed that the Arabic teaching method used in Junior High school Muhammadiyah of Makassar was the method of muhadatsah, qawa'id, mubasyarah, muthola'ah, and insha. As for the results of the study regarding the effect of the Arabic teaching method on the interest in learning Arabic in Junior High school Muhammadiyah of Makassar, it can be concluded that the level of understanding of Arabic students with the methods used by the teacher in the teaching and learning process is very good and increasing, the results can be seen from the questionnaire results that 82, 5% are interested in learning Arabic with the methods used by the teacher, 10% are less interested, and 7.5% are not interested in learning Arabic with the methods used by the teacher.Keywords: Influence, methods, interests, teaching Arabic